2000
DOI: 10.1210/en.141.7.2309
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen Receptor   in Hematopoietic Stem Cell Development and B Lymphocyte Maturation in the Male Mouse

Abstract: Although estrogens and estrogen receptors (ERs) are known to function in the male brain and reproductive tract, few studies have evaluated their involvement in the male hematopoietic and immune systems. This study was undertaken to determine the role of ERalpha in hematopoietic progenitor and B lymphocyte maturation. ERalpha knockout (ER-/-), wild-type (ER+/+), and radiation chimeric (ERalpha positive or negative in either nonhematopoietic or hematopoietic elements, or both) male mice were used to determine ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 0 publications
6
70
0
Order By: Relevance
“…Interpretation of changes in DTH responses in these mice, however, would be complex since estrogen receptor knockout mice have been shown to have altered immune development as well as function (Staples et al 1999, Thurmond et al 2000. No known studies on the immunity of androgen knockout mice have been published so far, but one might expect similar complications to interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of changes in DTH responses in these mice, however, would be complex since estrogen receptor knockout mice have been shown to have altered immune development as well as function (Staples et al 1999, Thurmond et al 2000. No known studies on the immunity of androgen knockout mice have been published so far, but one might expect similar complications to interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…17β-estradiol treatment reduces cμ+ pre-B cells, associated with a decrease in Ig gene rearrangements and rag1 transcripts (62). It also has been demonstrated that ERα is predominantly responsible for mediating 17β-estradiol induced changes in B-cell precursors (63,64). These findings suggest that 17β-estradiol exerts negative influence on the production of B-lineage cells by modifying the differentiation, proliferation, and survival of early B-cell precursors.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…While some studies indicate that ERβ is the main negative regulator of hematopoietic progenitor cells [60,64], others suggest that this effect can be mediated through either ERα or ERβ [58,65]. The decreased lymphopoiesis may reflect an intrinsic B-cell response to estrogen of early lymphoid progenitors [62,66] and/ or indirect estrogen-dependent regulation of production and secretion of cytokines, such as IL-7, required for the development of early B lymphopoietic stages [58,66]. Furthermore, engagement of ERα, seems to be a trigger for autoimmunity and leads to breakdown in B-cell tolerance, with increased survival to immunocompetence of high-affinity autoreactive B lymphocytes.…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 99%
“…For instance, gender has been shown to be an important and independent predictor of clinical outcome and survival in cutaneous melanoma, with premenopausal females (but not women older than 60 years) experiencing an improved prognosis [72,73]. The presence of sex steroid receptors in hematopoietic elements [24,58,66], as well as thymic and BM stromal cells [74][75][76] suggests that they may have a direct or indirect effect on immunity and hematopoiesis. The sexual dimorphism of the immune response could be modulated by differences in T cell receptor signaling, expression of activation molecules on T lymphocytes and antigenpresenting cells [77], transcription or translation of cytokine genes, or lymphocyte homing [20].…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 99%